Investigation of systems of differential equations with delays and constraints imposed on the delays and derivatives of the solutions - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.929; 517.958:531–133 We establish conditions for the existence and uniqueness of the solutions of nonlinear systems of differential equations with delays and restrictions imposed on the delays and derivatives of the solutions.